Stres in osebna ocena zdravja zaposlenih v igralništvu - Mlinar, Suzana (Zdravstveno varstvo, 2009)
Objective: The aim of the study was to determine differences in the workplace characteristics and self-estimated health status of the Hit Park Casino employees by gender and frequency of stress experiences. Methods: The study included 251 employees, aged 18 to 58 years; 47.4 % of them were men and 52.6 %, women. The sample of variables included socio-demographic data, workplace characteristics, stress experience and self-evaluated health status. Basic statistical parameters, CHI2 and SPSS 15.0 for Windows were used for statistical analysis. Results: The majority of employees (45.8%) experienced occasional stress. Those individuals who never experienced stress viewed their health as excellent (p = 0.014); and reported less health problems (p = 0.024) than others. The respondents who reported occasional stress rated their health as much better than others their age. Conclusion: Individuals whooften experience stress need to become aware of the importance of being more active in adopting healthy lifestyles.
Keywords: delovno mesto; igralništvo; poklicni stres; stres; zdravje